2008
DOI: 10.1504/ijesb.2008.017396
|View full text |Cite
|
Sign up to set email alerts
|

How franchiser and franchisee relationships affect franchisees' satisfaction? The importance of fairness, communication and trust as ethical bases of relationship marketing

Abstract: Few empirical studies cover the theme of franchisees' satisfaction. This paper investigates the impact of the nature of relationship between franchisers and franchisees on franchisees' satisfaction. Research data have been collected by surveying 400 French franchisees. Surprisingly, this analysis shows that intangible factors in a franchise system are as important as the franchiser's support or even more important than the support. The article discusses implications of the study's results for future research a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In particular, previous studies about franchise relationship only stresses on the procedural fairness disregarding business performance, interaction and informational aspect (Brown et al, 2006;Griffith et al, 2006;Kumar et al, 1995;Yilmaz et al, 2004). Then, as existing literature about the direct and indirect relationship between the franchisor and the franchisee which are dealing with fairness is extremely limited (Croonen, 2010;Grace et al, 2013;Guilloux et al, 2008), this study fills this gap by examining the impact of the four separate types of fairness in the franchise system on the relationship quality and performance (re-contract intention).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, previous studies about franchise relationship only stresses on the procedural fairness disregarding business performance, interaction and informational aspect (Brown et al, 2006;Griffith et al, 2006;Kumar et al, 1995;Yilmaz et al, 2004). Then, as existing literature about the direct and indirect relationship between the franchisor and the franchisee which are dealing with fairness is extremely limited (Croonen, 2010;Grace et al, 2013;Guilloux et al, 2008), this study fills this gap by examining the impact of the four separate types of fairness in the franchise system on the relationship quality and performance (re-contract intention).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies report interpersonal fairness by binding interpersonal fairness and informational fairness (Ferguson et al, 2014;Greenberg, 1990). Second, previous studies about the direct and indirect relationship between the franchisor and the franchisee dealing with fairness are extremely limited (Croonen, 2010;Grace, Weaven et al, 2013;Guilloux et al, 2008). Croonen (2010) approached the fairness concept quantitatively in his study whereas Grace et al (2013) did not measure the fairness indirect way but reported that fairness affects the performance and the nature of the relationship between the franchisor and the franchisee.…”
Section: Food Service Franchise Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…There is also a separate stream of literature exploring the role of fairness in the context of a channel relationship (Kumar et al , 1995; Lund et al , 2013). Even though the Marketing Science Institute (2014-2016) included “perceived fairness” on its list of research priorities for 2014-2016, yet little research has explored the role of fairness in the context of a franchisor–franchisee relationship (Croonen, 2010; Guilloux et al , 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…It can help to make it possible to better frame and manage customer data in compliance with the regulations and in the joint interest of the different parties to the exchange. Indeed, although the franchisor–franchisee relationship has been approached by several researchers (Monroy and Alzola, 2005; Guilloux et al , 2008) and the management of customer data has been the subject of study by legal and information system researchers (Kim and Kim, 2009; Peltier et al , 2013), customer data management in franchise networks has been very little studied (Yerimpasheva and Balgabayeva, 2020), perhaps because of its complexity and sensitivity, the diversity of stakeholders involved in the franchisor–franchisee–customer exchange process and the variety of questions that it raises. For this reason, this research work proposes to answer the following main question: “ How important are the characteristics of the franchisor-franchisee relationship regarding the management of customer data in achieving positive marketing performance?…”
Section: Introductionmentioning
confidence: 99%